دور الإعلام في توعية الجمهور بالمدن الذكية لتعزيز التنمية المستدامة - الغمراوي، رجاء Alghamrawi, Raja; عبدالحميد، غادة محمود Abdulhamid, Ghadah Mahmoud (جامعة القاهرة - كلية الإعلام, 2022)
انطلاقا من أدبيات التنمية المستدامة تم التوصل إلى أن المدن الذكية كأحدي ابتكارات عصر تكنولوجيا المعلومات والتي تعد إحدى متطلبات تحقيق التنمية المستدامة في المجتمعات المتنوعة؛ حيث نتناول استدامة المدن كأحدي متطلبات التنمية المستدامة؛ بالإضافة إلى التعرف على المدن الذكية المستدامة باعتبارها من آليات التحول لتحقيق التنمية المستدامة المتمثلة في (النقل النظيف والمباني الذكية والطاقة المتجددة وإدارة المياه والنفايات وإعادة تدويرها والإدارة المستدامة والحوكمة مع مراعاة تدابير ومعايير التنمية المستدامة لتطبيق التكنولوجيات الجديدة والابتكار) ثم التطرق إلى التجربة المصرية في التحول إلى المدن الذكية المستدامة، ودور الإعلام في تدعيم الأفراد والمجتمعات؛ لتحسين جودة الحياة كأحد متطلبات التنمية المستدامة. لذلك جاءت الدراسة الراهنة، لتلقي الضوء على تلك التحديات التي تتيح فرص عمل وتحقيق الرخاء للجمهور. مشكلة الدراسة وتساؤلاتها: تتلخص مشكلة الدراسة في الإجابة على التساؤل الرئيسي لها هل للإعلام دور في تنمية وعي الجمهور بأهمية إقامة المدن الذكية؟ ومن خلال الإجابة على السؤال الأساسي للبحث نستطيع أن نطرح مجموعة من التساؤلات 1. ما اتجاهات الجمهور وانطباعهم نحو إيجابيات وسلبيات المدن الذكية؟ 2. ما المستوى التعليمي للشخصيات التي تجسد الأنماط السلوكية المستحدثة نحو المدن الذكية؟ 3. ما هي مرحلة تبني الجمهور للمدن الذكية هل هي مجرد المعرفة أم الاهتمام أم التقييم أم التجربة؟ 4. إلى أي فئة ينتمي الجمهور عند التعامل مع المدن الذكية (المبتكرون، المتبنون الأوائل، الأغلبية المبكرة، الأغلبية المتأخرة، المتلكئون؟ أهمية الدراسة: تأتي أهمية الدراسة من أنها تعالج التحول الرقمي للمدن حتى نستطيع تحقيق أهداف التنمية المستدامة ورؤية 2030 ولن تتحقق تنمية أو تحول رقمي دون وعي الجمهور بأهمية إقامة المدن الذكية أو تحويل المدن الموجودة حاليا إلى مدن ذكية وذلك لمواكبة عصر الرقمنة. النتائج العامة للدراسة: 1. اثبت الدراسة تفوق في وسائل الإعلام الرقمية على الوسائل التقليدية حيث تحظى باستمرارية المتابعة من جمهور العينة أثر مما يستوجب الآخذ في الاعتبار أهمية استخدام كافة الوسائل الإعلامية الرقمية في التوعية بأهمية إنشاء المدن الذكية وأيضا العمل على زيادة فاعلية الوسائل الإعلامية التقليدية كوسيلة لزيادة الوعي بالعائد من إنشاء المدن الذكية على الفرد والمجتمع. 2. توصلت النتائج إلى إمكانية استخدام كل من (صفحات مواقع التواصل الاجتماعي والصحف الإلكترونية، المنصات الرقمية كاليوتيوب) بشكل منهجي علمي باعتبارها وسيلة اتصال تحظى بنسبة قبول واهتمام كبيرة من جانب العينة مما يزيد من فاعليتها كأداة للتوعية بأهمية المدن الذكية. 3. اثبت نتائج الدراسة توافر قاعدة معرفية كبيرة لدى الجمهور بالمدن الذكية مما يساعد على كثرة استخدام وسائل زيادة الوعي بأهمية إنشاء المدن الذكية المستدامة هامة لبناء مجتمع أفضل ومن اجل تحقيق العائد الاقتصادي، وتحسين البيئة، لرفع معيشة الأفراد والمجتمع. 4. اعتماد اقل من نصف العينة على وسائل الإعلام كمصدر رئيسي للمعلومات عن المدن الذكية يعزز كثيرا الدور المنوط بوسائل الإعلام في القيام به من اجل التوعية بأهمية المدن الذكية مما يتعين على القائم بالاتصال التنوع في استخدم الأساليب المؤثرة في الجمهور. 5. توصلت الدراسة أن نصف العينة ترى عدم كفاية التناول الإعلامي للقضايا المرتبطة بالمدن الذكية مما يساعد القائم بالاتصال على تطوير الأساليب الاتصالية المستخدمة. Based on the literature on sustainable development, it has been concluded that smart cities are one of the innovations of the IT era, which is one of the requirements for achieving sustainable development in diverse societies, where we address the sustainability of cities as one of the requirements of sustainable development, in addition to identifying smart sustainable cities as transformation mechanisms for achieving sustainable development (clean transport, smart buildings and renewable energy). Water and waste management and recycling, sustainable management and governance taking into account the measures and standards of sustainable development for the application of new technologies and innovation) and then addressing the Egyptian experimentation in the transition to smart sustainable cities, and the role of the media in strengthening individuals and communities; Therefore, the current study highlights those challenges that provide jobs and prosperity for the public. The problem of the study and its questions: The problem of the study is to answer the main question of whether the media has a role in developing public awareness of the importance of establishing smart cities? And by answering the basic question of research, we can ask a bunch of questions. 1- What are the public impression towards the positives and disadvantages of smart cities? 2- What is the educational level of characters that embody the behavioural patterns developed towards smart cities? 3- What is the stage of public adoption of smart cities, is it just knowledge, interest, evaluation or experience? 4- To which category does the public belong when dealing with smart cities (innovators, early adopters, early majority, late majority, owners? The importance of the study: The importance of the study comes from addressing the digital transformation of cities so that we can achieve the Sustainable Development Goals and Vision of 2030 and will not achieve digital development or transformation without the public awareness of the importance of establishing smart cities or turning existing cities into smart cities in order to keep pace with the age of digitization. General results of the study: 1- The study proved superior in digital media to traditional means where continuity of follow-up from the sample audience has an impact, which requires taking into account the importance of using all digital media in raising awareness of the importance of creating smart cities as well as working to increase the effectiveness of traditional media as a means of increasing awareness of the return from the establishment of smart cities on the individual and society. 2. The results found that both (social media pages, online newspapers, digital platforms such as YouTube) could be used systematically scientifically as a means of communication that receives a high level of acceptance and attention from the sample, which increases its effectiveness as a tool to raise awareness of the importance of smart cities. 3. The results of the study proved the availability of a large knowledge base among the public in smart cities, which helps to use the many means to raise awareness of the importance of creating sustainable smart cities important to build a better society and to achieve economic return, improve the environment, to raise the lives of individuals and society. 4. The reliance of less than half of the sample on the media as a major source of information on smart cities greatly enhances the role of the media in raising awareness of the importance of smart cities, which is what the contact has to use diversity in the use of methods that influence the public. 5. The study found that half of the sample considers that the media handling of issues related to smart cities is insufficient, which helps the contact person to develop the communication methods used.
Keywords: التنمية المستدامة -- المدن الذكية -- الوعي التنموي -- وسائل الإعلام الرقمية